Super-toughed polylactide/poly (butylene adipate-co-terephthalate) blends in-situ compatibilized by poly (glycidyl methacrylate) with different molecular weight. (November 2022) - Xu, Pengwu; Zhang, Ce; Tan, Shuai; Niu, Deyu; Yang, Weijun; Sun, Yujie; Ma, Piming
Highlights: PGMA with different molecular weight was synthesized as reactive compatibilizers. Super-toughed and biodegradable PLA/PBAT blends were prepared by reactive melt blending. Interface-localized copolymers markedly enhance interfacial adhesion and compatibility between PLA and PBAT. New ideas for the design of efficient compatibilizers for biodegradable polyesters were provided. Abstract: Poly (glycidyl methacrylate) (PGMA) with different molecular weight (Mw ) were synthesized and used as reactive compatibilizers to prepare super-toughed and biodegradable polylactide/poly (butylene adipate-co-terephthalate) (PLA/PBAT) blends. The epoxy group of PGMA can in-situ react with the end groups of PLA and PBAT, thus improving the interfacial adhesion between PLA and PBAT by forming PLA-g-PBAT copolymers. The effects of Mw and content of PGMA on phase morphology and physical properties of the PLA/PBAT blends were systematically investigated. The Mw takes an important role in its dispersion between the PLA and the PBAT phases, and consequently influences the mechanical performance. Interestingly, the PBAT domain size in the PLA matrix decreased from 3.7 μm to 1.7 μm after incorporation of even 0.5 wt% PGMA with a Mw of 44 kDa, and the in-situ improved compatibility leading to that the tensile strength and elongation at break of the PLA/PBAT blends increased by 35% and 87%, respectively. On the contrary, the size of the PBAT domains increased to > 5 μm and the mechanical properties of the PLA/PBAT blends decrease obviously with the same content but a higher Mw (90 kDa) of PGMA, because the higher Mw PGMA dispersed and reacted solely with the PLA matrix, and the enhanced melt viscosity of the PLA matrix could result in a non-uniform dispersion of the PBAT. Therefore, this work provides new insight in designing and preparation of efficient compatibilizers for biodegradable polyesters.